Erythrocyte-derived extracellular vesicles aggravate inflammation by promoting the proinflammatory macrophage phenotype through TLR4–MyD88–NF-κB–MAPK pathway. Issue 4 (12th April 2022) - Gao, Yuhan; Jin, Haiqiang; Tan, Hui; Cai, Xiaodong; Sun, Yongan
Abstract: Transfusion of stored erythrocytes is associated with the increased risk of morbidity and mortality in critical infections, but the mechanism is incompletely understood. Previous studies have suggested that RBC-derived extracellular vesicles (EVs) may be potential risk factors for the occurrence of transfusion-related immunomodulation. The purpose of our study was to evaluate the effects of RBC-derived EVs under inflammatory conditions and explore the underlying mechanisms. In vivo, the activity of EVs was evaluated in cecal ligation and puncture (CLP)-induced sepsis. Our results showed that EVs significantly aggravated the inflammatory response to sepsis in serum and lung tissue by promoting the production of the proinflammatory factors tumor necrosis factor-α (TNF-α）-interleukin-6(IL-6), and interleukin-1β (IL-1β) and reduced the survival rate of septic mice in vivo. Importantly, adoptive transfer of EVs-pretreated bone marrow-derived macrophages (BMDMs) obviously aggravated systemic proinflammatory factors in mice after CLP surgery. In vitro, the proinflammatory properties of EVs were shown to elevate TNF-α, IL-6, and IL-1β levels in lipopolysaccharide (LPS)-stimulated BMDMs. Moreover, EVs promoted LPS-induced macrophage polarization into a proinflammatory phenotype. The underlying mechanism might involve EV-mediated up-regulation of TLR4–MyD88–NF-κB–MAPK activity to favor macrophage cytokine production. Graphical Abstract: EVs aggravate inflammation by promoting the proinflammatory macrophage phenotype with upregulation of NF-κB and MAPK activity to favor macrophage cytokine production.